Public interest as understood by the Institute of Certified Public Accountants of Kenya - an analysis in light of the common good - Migue, Speranza Agnes Wangari (Strathmore University, 2019)
The Institute of Certified Public Accountants of Kenya (ICPAK) states, in the 2006 ICPAK Code of Ethics for Professional Accountants, the main role of accountants is to uphold the public interest. This research sought to determine the meaning of public interest from the point of view of ICPAK and as understood by a small number of ICPAK members. At the completion of this research, no official document presented by ICPAK on public interest existed. Therefore, on the premise that ICPAK adopted in full a Code of Ethics (CoE) issued by the International Federation of Accountants (IFAC), and, in the absence of any official clarification of terms in the adopted code by ICPAK, this research went back to IFAC to determine IFAC’s meaning of public interest, as presented in official documents published in 2012. The views of the ICPAK members were harnessed using open-ended questions through interviews. This study, using the concept of common good based on the Aristotelian tradition, analysed the meaning of public interest as proposed by ICPAK and as understood by ICPAK members. This study is exploratory in nature from two aspects: one, in order to examine ideas as proposed by IFAC and understood by ICPAK members; and, two, by analysing the findings using the concept of the common good based on the Aristotelian tradition. The aforementioned findings indicated that both the terms ‘public’ and ‘interest’, focus on specific groups, and specific economic needs, respectively. Thus, accountants do not serve all society. From this point of view, the interviewed ICPAK members admitted the impossibility of accountants’ ability to serve all society. Nonetheless, from the analysis, using the common good, the conclusion reached indicated that if accounting professionals espouse certain virtues, accountants really do serve all society.
Thesis submitted in partial fulfillment of the requirements for the Degree of Masters in Applied Philosophy and Ethics (MAPE) at Strathmore University, Kenya
Keywords: Public interest; Common good; ICPAK; IFAC